Oxygen demand during mineralization of aquatic macrophytes from an oxbow lake - Bianchini Jr.,I. (2008)
This study presents a kinetic model of oxygen consumption during aerobic decomposition of detritus from seven species of aquatic macrophytes: Cabomba furcata, Cyperus giganteus, Egeria najas, Eichhornia azurea, Salvinia auriculata, Oxycaryum cubense and Utricularia breviscapa. The aquatic macrophytes were collected from Óleo Lagoon situated in the Mogi-Guaçu river floodplain (SP, Brazil). Mineralization experiments were performed using the closed bottles method. Incubations made with lake water and macrophytes detritus (500 mL and 200 mg.L-1 (DM), respectively) were maintained during 45 to 80 days at 20 °C under aerobic conditions and darkness. Carbon content of leachates from aquatic macrophytes detritus and dissolved oxygen concentrations were analyzed. From the results we concluded that: i) the decomposition constants differ among macrophytes; these differences being dependent primarily on molecular and elemental composition of detritus and ii) in the short term, most of the oxygen demand seems to depend upon the demineralization of the dissolved carbon fraction.